LIU ZEHUA 劉澤華 (1935–2018). (September 2019) - Pines, Yuri
Abstract: This obituary surveys the biography and major works of Liu Zehua, a leading scholar of China's intellectual history, political thought, and political culture. It explores the impact of Liu Zehua's personal experience, in particular the upheavals of the Cultural Revolution, on his conceptualization of Chinese political culture as subjugated to the overarching principle of monarchism. Liu Zehua's critical engagement with China's past distinguished him from proponents of revival of traditional values and made him one of the powerful opponents of cultural conservatives in China. 提要: 這篇悼文介紹中國著名學者劉澤華先生及其主要著作。劉澤華先生是中國政治思想和政治文化領域的大家。本文探討劉澤華先生的個人經歷，尤其是他在文化大革命中經歷的劇變，對其歷史觀的影響。先生的經歷引發其思考：爲什麽中國傳統政治文化一直屈服於王權主義思想及實踐？劉澤華對中國歷史的批判性解讀使他有別於支持傳統價值觀復興的學者們， 成爲中國文化保守主義的主要反對者之一。